Segmental resection with primary anastomosis is not always safe in splenic flexure perforation. (December 2016) - Weledji, Elroy; Mokake, Martin; Sinju, Motaze
Abstract Background Familial adenomatous polyposis (FAP) is caused by a rare mutation of the adenomatous polyposis coli gene on Chromosome 5q. The risk of colorectal cancer in patients with FAP is nearly 100 % and intensive endoscopic surveillance or prophylactic colectomy are mandatory. If extensive endoscopic surveillance is chosen, there is a cumulative risk of perforation and bleeding especially after polypectomy. We discussed the problems and options in the management of the late diagnosis of an iatrogenic perforation of the splenic flexure complicating endoscopic surveillance in FAP. Case presentation We present a 35-year-old black African man with FAP who sustained a splenic flexure perforation following a colonoscopic polypectomy of a suspicious lesion. He underwent a splenic flexure resection and primary anastomosis that dehisced and the patient benefited from an emergency definitive colectomy and ileorectal anastomosis. Conclusions Resection with primary anastomosis following iatrogenic perforation of the splenic flexure is not safe because of a high chance of anastomotic dehiscence. Following a late diagnosis in an unstable patient exteriorization of the perforation as a stoma is a better option prior to a definitive prophylactic colectomy.